Annexin A6 Is Critical to Maintain Glucose Homeostasis and Survival During Liver Regeneration in Mice. Issue 6 (23rd December 2020) - Alvarez‐Guaita, Anna; Blanco‐Muñoz, Patricia; Meneses‐Salas, Elsa; Wahba, Mohamed; Pollock, Abigail H.; Jose, Jaimy; Casado, Mercedes; Bosch, Marta; Artuch, Rafael; Gaus, Katharina; Lu, Albert; Pol, Albert; et al.
Abstract : Background and Aims: Liver regeneration requires the organized and sequential activation of events that lead to restoration of hepatic mass. During this process, other vital liver functions need to be preserved, such as maintenance of blood glucose homeostasis, balancing the degradation of hepatic glycogen stores, and gluconeogenesis (GNG). Under metabolic stress, alanine is the main hepatic gluconeogenic substrate, and its availability is the rate‐limiting step in this pathway. Na + ‐coupled neutral amino acid transporters (SNATs) 2 and 4 are believed to facilitate hepatic alanine uptake. In previous studies, we demonstrated that a member of the Ca 2+ ‐dependent phospholipid binding annexins, Annexin A6 (AnxA6), regulates membrane trafficking along endo‐ and exocytic pathways. Yet, although AnxA6 is abundantly expressed in the liver, its function in hepatic physiology remains unknown. In this study, we investigated the potential contribution of AnxA6 in liver regeneration. Approach and Results: Utilizing AnxA6 knockout mice (AnxA6 −/− ), we challenged liver function after partial hepatectomy (PHx), inducing acute proliferative and metabolic stress. Biochemical and immunofluorescent approaches were used to dissect AnxA6 −/− mice liver proliferation and energetic metabolism. Most strikingly, AnxA6 −/− mice exhibited low survival after PHx. This was associated with an irreversible and progressive drop of blood glucose levels. Whereas exogenous glucose administration or restoration of hepatic AnxA6 expression rescued AnxA6 −/− mice survival after PHx, the sustained hypoglycemia in partially hepatectomized AnxA6 −/− mice was the consequence of an impaired alanine‐dependent GNG in AnxA6 −/− hepatocytes. Mechanistically, cytoplasmic SNAT4 failed to recycle to the sinusoidal plasma membrane of AnxA6 −/− hepatocytes 48 hours after PHx, impairing alanine uptake and, consequently, glucose production. Conclusions: We conclude that the lack of AnxA6 compromises alanine‐dependent GNG and liver regeneration in mice.